Is there an asymmetric impact of housing on output? - Tsung-Hsien Michael Lee; Wenjuan Chen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Numerous papers have tried to understand housing's role in the economy and have not reached an agreement. In this paper we turn to the asymmetric relationship between housing and the overall economic activity. We find that the relation between building permits and GDP is regime-dependent. Causality analysis suggests that the housing variable leads output only in the regime associated with periods when the housing and business cycles are experiencing contractions. Our findings not only echo the argument that housing leads the business cycles, but also show that it has time-varying effect on the overall economic activity.
Keywords: C32; C34; E32; 330; Housing; Business Cycles; Regime-switching; Causality